2022
DOI: 10.3389/fcvm.2022.963731
|View full text |Cite
|
Sign up to set email alerts
|

The clinical outcomes of reni-angiotensin system inhibitors for patients after transcatheter aortic valve replacement: A systematic review and meta-analysis

Abstract: AimsThe objective of our systematic reviews and meta-analysis is to evaluate the clinical outcomes of RAS inhibitors for patients after TAVR.Methods and resultsWe performed a comprehensive search for Embase, Pubmed, and Cochrane databases from inception to May 1, 2022. The analysis of all outcomes was performed using the random-effects model. In total, 7 articles with a total of 32,585 patients (RAS inhibitor, N = 14,871; Controls, N = 17,714) were included in our study. There was a significantly lower rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The beneficial effect of targeted medication at hospital discharge has already been demonstrated for ACEI/ARB ( 8 , 16 ) and statins ( 17 ) and demonstrates parallels to the effect in patients with HF. It is interesting to note that the ACEI/ARB regimen might be effective not only in stable patients without any prior CD but also in those with prior CD and even in those hospitalized for acute CD.…”
Section: Discussionmentioning
confidence: 81%
“…The beneficial effect of targeted medication at hospital discharge has already been demonstrated for ACEI/ARB ( 8 , 16 ) and statins ( 17 ) and demonstrates parallels to the effect in patients with HF. It is interesting to note that the ACEI/ARB regimen might be effective not only in stable patients without any prior CD but also in those with prior CD and even in those hospitalized for acute CD.…”
Section: Discussionmentioning
confidence: 81%
“…Until a few years ago, ACEIs/ARBs were considered potentially harmful and even contraindicated in severe AS because they could potentially cause a rapid and harmful decrease in BP levels (6). However, a recent metaanalysis that included observational and randomized evidence indicated that ACEIs/ARBs could be harmless and could even be helpful for treating AS (4,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent meta‐analysis of seven studies on outcomes of RAS inhibitors following TAVI, the authors showed that prescription of RAS inhibitors after TAVI resulted in lower all‐cause and cardiovascular mortality and rehospitalization for heart failure. 11 In our study, which is the most updated meta‐analysis by adding two recent studies, 5 , 9 we compared additional outcomes including stroke and myocardial infarction rate, and also two postprocedural parameters (AKI and new pacemaker implantation). In our analysis, we also combined all the reported HRs and calculated an overall hazard for all‐cause mortality.…”
mentioning
confidence: 99%